2007
DOI: 10.3892/or.17.6.1437
|View full text |Cite
|
Sign up to set email alerts
|

Timing of apoptosis onset depends on cell cycle progression in peripheral blood lymphocytes and lymphocytic leukemia cells

Abstract: Abstract. Apoptosis results in cell death within 10 min after initiation by Bcl-2 family proteins and mitochondria; however, cells enter the apoptotic pathway at different elapsed times after being triggered. Intrinsic factors related to chemical or physical cell damage can initiate apoptosis at a specific cell cycle phase; it is not clear whether cells insulted via an extrinsic pathway also die at a specific cell cycle phase, or how apoptosis is related to cell cycle progression in cells. To illustrate the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
(29 reference statements)
2
20
0
Order By: Relevance
“…The expressions of apoptosis-related proteins Bcl-2, caspase-3 and caspase-9 were also consistent with the findings. The results of the study were coincident with those reported by Feng et al [21] , who reported that quiescent PBLs were insensitive to apoptosis inducers. This finding indicated that the cell cycle status was a prerequisite for apoptosis, and apoptosis was a cell cycle event.…”
Section: Discussionsupporting
confidence: 90%
“…The expressions of apoptosis-related proteins Bcl-2, caspase-3 and caspase-9 were also consistent with the findings. The results of the study were coincident with those reported by Feng et al [21] , who reported that quiescent PBLs were insensitive to apoptosis inducers. This finding indicated that the cell cycle status was a prerequisite for apoptosis, and apoptosis was a cell cycle event.…”
Section: Discussionsupporting
confidence: 90%
“…Direct LC-MS analysis of the PC-eluted, partially purified (Sep pak C 18 cartridge) extract was possible without any risk of mass fragmentation overlapping within compounds. Investigation of the LC-MS ion fragments showed that the 5 compounds (Table 2) of the 5 resolved peaks were distinct in their fragmentation patterns showing respective molecular weights, however with different absorption maxima matching with earlier reports (Downey & Rochfort, 2008 that of compound 5 in the present study, whereas compound 2 was the second major one reported by Adje et al (2008).The high content (88 mg/100 g) of Cyanidin-3-O-rutinoside(4) has been of great current interest because of its various biological roles (Akkarachiyasit, Yibchok-Anun, Wacharasindhu, & Adisakwattana, 2011;Chitra, Ilango, Rajanandh, & Soni, 2010) of antioxidative, anticancer, antiinflammatory, anti-diabetic and in selectively killing leukemic cells by induction of oxidative stress (Feng et al, 2007). [1][2][3]7,12,3,5,7,9,11,13,15, [1][2][3]7,12,3,5,7,9,11,13,15, 4-[18-(4-hydroxy-2,6,6-trimethyl-1-cyclohexenyl)-3,7,12,16-tetramethyl-octadeca-1, 3,5,7,9,11,13,15,17-nonaenyl]-3,5,5-trimethyl-cyclohex-3-en-1-ol 7,12,16,20,3,5,7,9,11,13,15,17,19,-3,5,5-trimethylcyclohex-3-en-1-ol β-Cryptoxanthin C 40 H 56 O 552.85 (R)-3,5,5-Trimethyl-4-[3,7,12,16-tetramethyl-18-(2,6,6-trimethylc...…”
Section: Hplc-ms Analysis Of Anthocyaninsmentioning
confidence: 80%
“…For Jurkat T cells, one can argue that these cells-due to their malignancy-already proliferate at a maximum degree and cannot be further stimulated, a fact we also observed for stimulation with PHA, a strong T cell mitogen which was nevertheless unable to stimulate further proliferation in Jurkat T cells (data not shown). However, the stimulating effect of caffeine on the proliferation of already stimulated PBL can be explained by the reported ability of the methylxanthine to abolish cell cycle checkpoints [45]. As already mentioned, unstimulated PBL are resting in the G 0 phase of the cell cycle after isolation and therefore show per se no mitotic and cell cycle activity.…”
Section: Discussionmentioning
confidence: 99%